Avaliação da bioacessibilidade de selênio em grãos de arroz biofortificados pela aplicação via solo ou foliar de espécies inorgânicas do elemento - Lima, Alexandre Boari de (2022)
Selenium is a micronutrient for human nutrition that has gained distinction in the world scientific scenario, because its deficiency is related to some human diseases. Recent studies have not only brought a better understanding of the functions of the Se in the human body, but also proposed strategies to increase its intake, especially through food. Selenium biofortification studies in staple foods have been performed in recent decades. Several of these studies were successful in attaining to higher levels of this nutrient in food through biofortification. However, there are still few studies towards the evaluation of chemical species of this element that are accumulated in cereal grains. Research related to the assessment of the potentially bioavailable selenium fraction in these biofortified foods is even more scarce. It is important to perform bioaccessibility assays on biofortified foods to evaluate the efficiency of food biofortification using inorganic selenium species, such as selenate and selenite. Rice, for example, is one of the most consumed staple foods in Brazil. Its biofortification, which will increase the content of the nutrient in the grain, can mitigate the problem of low selenium intake by most of the population that chooses rice as a staple food. Thus, the objective of this work was to determine the bioaccessible fraction of selenium in rice grains biofortified via soil or foliar with inorganic species of the element. For this purpose, an in vitro sequential extraction method was used to simulate the human gastrointestinal tract. The samples and extracts were submitted to microwave-assisted acid digestion. The determinations of total and bioaccessible levels were performed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) with dynamic reaction cell (DRC) using oxygen gas (O2). This study allowed us to conclude that the biofortification via leaf with sodium selenate and selenite were more effective in producing grains with higher selenium levels in the bioaccessible fraction. These content in rice grains were, on average, 61 ± 5 % of the total content and 44 ± 4 % of the total were extracted in the gastric stage of digestion. These results allow to conclude that the biofortification of rice grains, with inorganic forms of selenium, is also effective to increase the bioaccessible content of this element in food, but the amount to be applied to the soils or plant leaves must consider that the efficient fraction would be lower than the total amount based on the applied dose.